Zooplankton monitoring using a twin NORPAC net during the 58th Japanese Antarctic Research Expedition in austral summer 2016–2017 (National Institute of Polar Research, 2019)
As part of the monitoring program of the Japanese Antarctic Research Expedition (JARE), zooplankton sampling using a NORPAC (NORth PACific) standard net has been routinely carried out since JARE-14 (1972/73 season) to estimate the long-term trends of abundance, species composition and their temporal/spatial variation in the uppermost 150 m of the Indian Ocean sector of the Southern Ocean. Two separate monitoring surveys were completed during JARE-58 (December 2016 to March 2017). The icebreaker Shirase has a fixed schedule and route, travel down longitude 110ºE each December and return along 150ºE each March, making its voyages ideal for long-term monitoring work in this region. We present data from its 2016/2017 voyage. In additions, a transects by the T/V Umitaka-maru was also carried out along 110ºE longitude in January 2017. Thus, this report provides the latest zooplankton data, forming part of the long-term monitoring of zooplankton carried out by JARE in this region for the last 40 years. These transect data can be used as time series and/or seasonal sets.